Thermal Comfort of Ad-Du’a Mosque in Bandar Lampung City, Indonesia - Ai Siti Munawaroh; M. Ilyas Kurniawan; M. Khoirudin Rais; Thufail Amarullah (Jurnal Arsitektur, 2023)
The mosque is a place of worship for Muslims. Worship here is not merely a place to pray and recite the Koran, but activities that can get rewards and intercession in this world and the hereafter such as lectures, studies, discussions, and other positive things. The thermal in the room greatly affects the occupants and visitors. This study aims to determine the thermal at the Ad-Du’a Mosque. The method used is by measuring directly and gradually. The instrument used is thermohygrometers and anemometers. Thermohygrometer is used for measuring temperature and humidity. While, anemometer is used for measuring air velocity. The study was conducted at 5 points, 4 points in the room and 1 point on the terrace which is inside or on the terrace using artificial air conditioning (AC). The research results show that the thermal comfort inside the mosque does not meet SNI 03-6572-2001 and ASHRAE 55. The thermal comfort outside the mosque does not meet SNI 03-6572-2001, but meets ASHRAE 55.